O044 The association of the sleep regularity index with subjective cognitive function and academic skills in adolescents. (9th November 2022) - Hand, A; Stone, E J; Lu, S; Chacos, E; Carskadon, A M; Lockley, W S; Wiley, F J; Bei, B; Klerman, B E; Rajaratnam, M W S; Phillips, J K A
Abstract: High-level cognitive function is essential for academic performance in adolescents. While obtaining sufficient sleep duration has been shown to support cognitive function less is known about the role of sleep regularity in cognitive function. We investigated how sleep regularity relates to self-report cognitive function in 179 Year 7 students (M±SD=12.81±0.41 years, 56% females) in Australia. Sleep/wake timing was measured via wrist actigraphy and daily sleep diaries over two-school-weeks. Sleep regularity was measured using the Sleep Regularity Index (SRI) calculated via actigraphy measured sleep (SRI range = 58-95). Self-report cognitive function was measured using the PROMIS Paediatric Cognitive Function questionnaire, which requires participants to self-report cognitive performance over the last four-weeks. Academic skills were measured using two-subtests (reading comprehension and numerical operations) from the Weschler Individual Achievement Test – Third Edition (WIAT-III). We found that adolescents with more regular sleep self-reported better subjective cognitive function (β = .39, p = .001), even when controlling for age, sex, circadian phase assessed using DLMO, and total sleep time. In contrast, average total sleep time (range = 5.78-11.30 hours) alone was not associated with subjective cognitive function (β = .06, p = .99). Higher self-reported cognitive function was also associated with improved reading and numerical ability on the WIAT-III (β = .42, p =.04; β = .37, p =.02, respectively). The SRI did not predict performance on the WIAT (p >.05). Our findings suggest regular sleep may be important in supporting optimal cognitive functioning. These results have important implications for learning adolescence.